Acute and chronic changes in LV performance in patients with secondary severe mitral regurgitation undergoing percutaneous mitral valve repair. (4th February 2022) - Galli, E; Hubert, P; Panis, V; L"official, G; Vely, M; Donal, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The non-invasive assessment of myocardial work allows to evaluate left ventricular (LV) performance by considering the effect of LV load on LV deformation. Aim of this study is to evaluate the acute and chronic impact of percutaneous mitral valve repair (PMVR) on LV function, in patients with severe secondary mitral regurgitation (SMR). Methods and Results: 41 patients (age: 69 ± 10 years, females: 29%) with severe SMR (effective regurgitant orifice: 0.42 ± 0.16 cm2, regurgitant volume: 65 ± 325 ml) underwent PMVR according to current recommendations. Myocardial work indices were evaluated before the procedure, 2 days after the procedure and at 1-year follow-up.  PMVR was associated with an acute reduction in LV ejection fraction (LVEF), global longitudinal strain (GLS), and myocardial constructive work (MCW) and with a significant increase in myocardial wasted work (MWW). 1-year after the procedure, we did not observe significant LV reverse remodeling. GWE remained significantly impaired despite the small improvement in GCW, which can explain the absence of improvement in MWE and GLS. Interestingly, LVEF modestly increased compared with the post-procedural values, but remained significantly reduced compared to baseline values (Table1). Conclusions: In patients severe SMR undergoing PMVR, the acute reduction in LV preload causes a significant impairment of all parameters of LV performance. After 1-year, the absence of LV reverse remodelling is associated a significant impairment in GWW, without substantial improvement in the remaining parameters of LV function.